Indicators of the speed movement in juvenile in rowing on kayaks - Volodymyr Bogush; Sergiy Getmantsev; Oleksandr Yatsunskiy; Konstantin Bogatyirev; Oleg Verteleckiy; Oksana Reznichenko (Kharkiv State Academy of Physical Culture, 2018)
Purpose: to study the indicators of the physical quality of the speed and its constituent elements. Material & Methods: juvenile were examined in the age groups 11-12 years, 13-14 years, 15-16 years, 17-18 years, various sports qualifications, specializing in rowing on kayaks. According to the method of measurement of the effect of the training action developed by us, the tempo, time and speed of single movement, the frequency of movements were determined, and sensorimotor responses to sound and light stimuli were simulated in modeling the conditions of training and competitive activity. Results: the conducted researches characterize the individual psycho-physiological characteristics of the athlete's body. For the purposeful study and development of the physical quality of the speed in the training process, it is possible to use the proposed method for studying the effect of the training action. Formation and improvement of motor abilities in specific age ranges is carried out in connection with high rates of development of morphological and functional indicators in sensitive periods. The studied indicators of the physical quality of the rapidity and its constituent elements depend on the age, the level of general physical and functional readiness. Conclusion: for the improvement of motor qualities and the formation of rapidity of movements, the age periods under study are the most favorable prerequisites. As a result of the training process, the tempo, time, speed, frequency of movements, time of sensorimotor reactions to sound and light stimuli change.